Mixed convection of nanofluid filled cavity with oscillating lid under the influence of an inclined magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Science Bv, 2016)
In this study, mixed convection of an oscillating lid-driven cavity filled with nanofluid under the influence of an inclined uniform magnetic field was numerically investigated. The cavity is heated from below and cooled from above while side walls are assumed to be adiabatic. The top wall velocity varies sinusoidally while no-slip boundary conditions are imposed on the other walls of the cavity. The governing equations was solved by Galerkin weighted residual finite element formulation. The numerical investigation was performed for a range of parameters: Richardson number (10(-1) <= Ri <= 10(2)), Hartmann number (0 <= Ha <= 60), inclination angle of the magnetic field (0 <= gamma <= 90), non-dimensional frequency of the oscillating lid (0.001 <= St <= 1) and solid volume fraction of the nanoparticle (0 <= phi <= 0.04). It is observed that the flow and thermal patterns within the cavity are affected by the variation of these parameters. The heat transfer process becomes inefficient for high Strouhal number, high Hartmann number and high Richardson number. Maximum enhancement of averaged heat transfer and the damping of the convection within the cavity due to the Lorentz forces caused by magnetic field are attained for magnetic inclination angles of gamma = 90 degrees and gamma = 60 degrees. As the solid volume fraction of nanoparticles increases averaged heat transfer enhancement of 28.96% is obtained for volume fraction of phi = 0.04 compared to base fluid. (C) 2016 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Oscillating lid; Magnetic field; Nanofluids; Finite element method